2014
DOI: 10.1016/j.clinph.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Theta and delta band activity explain N2 and P3 ERP component activity in a go/no-go task

Abstract: Objectives Recent work indicates that the feedback negativity (FN) and P3 components from gambling feedback tasks can be understood as mixtures of functionally distinct processes occurring separately in theta and delta frequency bands. The current study was conducted to assess whether dissociable processes occurring in the theta and delta bands would similarly account for activity underlying N2 and P3 components in a go/no-go task. Methods The current study measured EEG signals from 66 participants during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
191
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(227 citation statements)
references
References 63 publications
36
191
0
Order By: Relevance
“…Despite this observation, there is some evidence that theta oscillations have a role response inhibition. In contrast with Mazaheri et al, 2009, several studies have reported higher theta power in no-go trials over go trials, although this may be driven by differences in task parameters (Harmony et al, 2009;Harper et al, 2014;Kirmizi-Alsan et al, 2006;Nakata et al, 2013). Thus it remains unclear what is the role for frontal theta in inhibition of a predominant response, and further, what cortical signals may contribute to cognitive control over habitual responding (cf.…”
Section: Introductionmentioning
confidence: 83%
“…Despite this observation, there is some evidence that theta oscillations have a role response inhibition. In contrast with Mazaheri et al, 2009, several studies have reported higher theta power in no-go trials over go trials, although this may be driven by differences in task parameters (Harmony et al, 2009;Harper et al, 2014;Kirmizi-Alsan et al, 2006;Nakata et al, 2013). Thus it remains unclear what is the role for frontal theta in inhibition of a predominant response, and further, what cortical signals may contribute to cognitive control over habitual responding (cf.…”
Section: Introductionmentioning
confidence: 83%
“…Especially, the event-related potential (ERP) studies have reported the most significant findings of the delta band related to cognitive processing [44], i.e., the associations of the P300 component with the cognitive process [46]. This relationship has been widely reported in the cognitive neuroscience literature.…”
Section: Eeg Low Frequencies With Cognitive Neuroscience Perspectivementioning
confidence: 97%
“…The EEG low frequency bands (delta and theta) have been reported by the cognitive neuroscientists as cognitive rhythms, and have been linked with cognitive and attention demanded tasks [43][44][45]. Especially, the event-related potential (ERP) studies have reported the most significant findings of the delta band related to cognitive processing [44], i.e., the associations of the P300 component with the cognitive process [46].…”
Section: Eeg Low Frequencies With Cognitive Neuroscience Perspectivementioning
confidence: 99%
“…This wave is usually modulated by correctly or incorrectly inhibited responses, with larger amplitudes for unsuccessfully stopped (US) than for successfully stopped (SS) responses (Dimoska, Johnstone, & Barry, 2006;Kok et al, 2004;Ramautar et al, 2006). Time-frequency data have shown that the N2 is associated with theta oscillations (around 4-7 Hz) over fronto-central scalp areas, an activity also related to conflict detection and error processing (Harmony, Alba, MarroquĂ­n, & GonzĂĄlez-Frankenberger, 2009;Harper, Malone, & Bernat, 2014;Kirmizi-Alsan et al, 2006;Luu, Tucker, & Makeig, 2004;MĂŒller & Anokhin, 2012). The neural generator of the N2 is presumed to be located around the dorsal portion of the anterior cingulate cortex (Botvinick, Cohen, & Carter, 2004;Braver, Barch, Gray, Molfese, & Snyder, 2001;Nieuwenhuis, Yeung, van den Wildenberg, & Ridderinkhof, 2003).…”
mentioning
confidence: 99%